Musik Indisch dalam Perspektif Poskolonial: Studi Kasus Karya Ki Hadjar Dewantara dan Constant van de Wall - Margi Ariyanti; Vissia Ita Yulianto; Royke B. Koapaha (Universitas Gadjah Mada, 2021)
Indisch music is a music that uses a combination of “Eastern” music idioms and “Western” music idioms in composition and popular in Dutch-East Indies era. This article analyses the composition of Indisch music composed by Ki Hadjar Dewantara, a well-known educational figure and composer in Indonesia and Constant van de Wall, a Javanese-Dutch composer in a postcolonial perspective. Using a qualitative method and with a music theory framework and a postcolonial theory framework, this article answers two research questions: the first is how Ki Hadjar Dewantara and Constant van de Wall in making their Indisch music works viewed in terms of their composition and the second is how the contestation of the struggle the power that is built into their piano composition in a postcolonial perspective. The composition of the two composers shows that Dutch colonialism in the Dutch East Indies has produced a mixed culture called Indisch culture which has become an arena of contestation and power struggle for the colonizers and colonized. Starting from this point, the authors hope that this article contributes to the world of piano education in Indonesia. Music teacher and student of music need to understand of postcolonial theory in addition to music theory and music history.Musik Indisch adalah jenis musik yang menggunakan perpaduan idiom musik “Timur” dan idiom musik “Barat” di dalam komposisinya dan populer di zaman Hindia-Belanda. Artikel ini menganalisis komposisi musik Indisch yang digubah oleh Ki Hadjar Dewantara, seorang tokoh pendidikan dan komponis terkenal di Indonesia dan Constant van de Wall, seorang komponis Jawa-Belanda. Dengan menggunakan metode kualitatif dan dengan kerangka teori musik dan kerangka teori poskolonial, artikel ini menjawab dua pertanyaan riset: yang pertama adalah bagaimana Ki Hadjar Dewantara dan Constant van de Wall dalam membuat karya musik Indischnya ditinjau dari bentuk komposisi mereka dan yang kedua adalah bagaimana kontestasi perebutan kuasa yang terbangun dalam komposisi piano mereka dalam perspektif poskolonial. Komposisi kedua komponis tersebut menunjukkan bahwa kolonialisme Belanda di Hindia-Belanda telah menghasilkan kebudayaan campuran yang bernama kebudayaan Indisch yang telah menjadi arena kontestasi dan pertarungan kuasa bagi si penjajah dan yang terjajah. Berangkat dari titik tersebut, penulis berharap artikel ini dapat berkontribusi dalam dunia pendidikan piano di Indonesia. Pemahaman teori poskolonial di samping teori musik dan sejarah musik penting dimiliki oleh guru dan siswa piano Indonesia.